Oxidative Stress and Methods for Its Correction in Patients with Acute Coronary Circulatory Disorders During Perioperative Direct Myocardial Revascularization - M. V. Chumakov; A. A. Yefremov; N. Yu. Zvereva; A. V. Dublev; V. Kh, Timerbayev; I. N. Fedotova; B. V. Davydov; N. I. Kharitonova; D. V. Malanyin; Ya. B. Brand (Общая реаниматология)
Objective: to study the effect of the antioxidant and cardioprotector mexicor on oxidative stress in patients with acute coronary circulatory disorders (ACCD) during perioperative direct myocardial revascularization. Subjects and methods. The study included 33 patients with ACCD who had undergone coronary bypass surgery. Two groups (a study group and a control one) were formed. Prior to surgery, all the patients received the maximum doses of antianginal and antihypertensive drugs. The study group patients additionally took mexicor. All patients were operated on under extracorporeal circulation and moderate hypothermia. Lipid peroxidation (LPO) indices were estimated via measurements of the serum levels of dienic conjugates, malonic dialdehyde, and the degree of serum lipid oxidability. The serum antioxidative system (AOS) was judged from the concentration of а-tocopherol and cerulo-plasmin. The oxidative stress coefficient K, an integral index, was calculated to evaluate LPO-AOS imbalance. Results. High oxidative stress was found to be detectable in patients with ACCD. Mexicor lowers oxidative stress, diminishes LPO-AOS imbalance, improves oxygen balance and cardiac contractility, and reduces the number of life-threatening cardiac arrhythmias. Conclusion. Mexicor diminishes oxidative stress in patients with ACCD in the perioperative period of coronary bypass surgery. Mexicor-induced stabilization of LPO positively affects better oxygen balance and cardiac contractility, thus reducing the number of perioperative complications. Key words: oxidative stress, dienic conjugates, malonic dialdehyde, а-tocopherol, ceruloplasmin, coronary bypass, acute coronary circulatory disorder, hemodynamics.